A study of working conditions in electroplating shops - A. M. Lazarenkov (Литьë и металлургия, 2019)
The results of the study of working conditions working in electroplating shops. It is shown that the main production factors of working conditions are noise, vibration, dust, gas contamination, relative humidity of air, the severity and intensity of the labor process. The results of the studies have shown that at all workplaces there are exceeding of the permissible values for noise level, the content of harmful substances in the air of the working environment when working directly with the galvanic baths, the relative humidity of the air. It is noted that the work performed on the severity and intensity of the labor process can adversely affect the health of workers.